Inserção da informática nos cursos de Arquitetura e Urbanismo do Brasil (1994 2006): diagnósticos, rebatimentos e perspectivas nas Instituições Federais de Ensino Superior do Nordeste: UFRN, UFPB e UFPE - Carreiro, Patricia de Oliveira Dias Porto (2007)
This work supports the formalist education s improvement of the Brazilian architect and urban designer through a better application and systematization of the computer science s teaching potentialities. The research analyzes the discipline introduction in the Brazilian courses: Computer Science Applied to Architecture and Urbanism (InfoAU) in the Architecture and Urbanism Courses of Brazil (CAUs). It goes since the discipline was obligated by the MEC s Regulation nr. 1.770 from 1994 until the CNE/CES Resolution nr. 6 from 2006; it comprehends the discipline implantation, development and current context, in order to get more detailed, the research analyses three federal universities from the Northeast of the country: UFRN, UFPB and UFPE. Once identified the historical educational needs in the CAUs, the study focus on the computer science s increasing potential as an agent of integration, communication, development and knowledge/data management. It points out new social perspectives for a better use of this tool/mechanism, which adequately structuralized and integrated, creates propitious educational and professional performance/recycling conditions and a propeller instrument of research and extension activities. Among this work, it is suggested the aggregation of elements, which are complementary to the InfoAU discipline s reorganization, throughout a computerization s plan for the CAUs, extensive to the professional formation, generating a virtuous cycle in several activities of the academic, administrative and, research and extension s departments. Therefore, the InfoAU in the Brazilian CAUs context was analyzed; the main solutions and problems found were systemized; the possibilities of computer science s uses inside AU ware structuralized, InfoAU discipline s improvement plan was also defined, as well as strategies for the implementation of the computerization s plan for the CAUs, which would guarantee its maintenance in a continuity perspective